Gender mainstreaming is just beginning - Deneke, S. (International Livestock Research Institute, 2011)
Seblewongel Deneke (CIDA) stated that many people are now talking about mainstreaming gender by including gender issues in research and policymaking. But new laws around gender are rarely enforced and research projects find it hard to expand capacity within extension workers and trainers and so meet the complex needs of women.